2013
DOI: 10.1016/j.meegid.2013.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Successful establishment and global dispersal of genotype VI avian paramyxovirus serotype 1 after cross species transmission

Abstract: The evolutionary history of avian paramyxovirus serotype 1 (PMV1), which includes the agents of Newcastle disease (ND), is characterized by a series of strain emergence events since viruses in this family were first recognized in the 1920s. Despite the importance of ND to the poultry industry, little is known about PMV1 strain emergence events and the subsequent dispersal and evolution of new strains. The genotype VI-PMV1 was first identified in the 1980s and has been named pigeon paramyxovirus-1 (PPMV1) becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 58 publications
7
24
0
Order By: Relevance
“…Indeed, the long period to the separation of class I and class II (approximately 234-244 years before the most recent isolates included in this study) and the small differences in CAI of these two classes provides evidence to suggest that the codon adaptation of APMV-1 is a slow process. As expected, class II genotype VI emerged from common ancestors with genotype VII (and genotypes XIII, XIV, XVII and XVIII) sometime between 1947 and 1951 (Table 2), that is in agreement with previously reported estimates (Chong et al, 2013;Sonora et al, 2015). Despite the differences in host of isolation for viruses of genotypes VI and VII, there are no large differences in codon usage or host adaptation, as it would be expected from a slow process of adaptation.…”
Section: Codon Usage Adaptation In Apmv-1 Is a Slow Processsupporting
confidence: 90%
“…Indeed, the long period to the separation of class I and class II (approximately 234-244 years before the most recent isolates included in this study) and the small differences in CAI of these two classes provides evidence to suggest that the codon adaptation of APMV-1 is a slow process. As expected, class II genotype VI emerged from common ancestors with genotype VII (and genotypes XIII, XIV, XVII and XVIII) sometime between 1947 and 1951 (Table 2), that is in agreement with previously reported estimates (Chong et al, 2013;Sonora et al, 2015). Despite the differences in host of isolation for viruses of genotypes VI and VII, there are no large differences in codon usage or host adaptation, as it would be expected from a slow process of adaptation.…”
Section: Codon Usage Adaptation In Apmv-1 Is a Slow Processsupporting
confidence: 90%
“…Poultry trade, however, does not explain all global movement of class II viruses. Rather, as demonstrated by our genotype VI-restricted model and a previously published genotype VI phylodynamic analysis [34], global migration of APMV-1 is also driven by transportation of pigeons, resulting in viral dispersal from Europe to other regions, including Africa and East Asia.…”
Section: Discussionmentioning
confidence: 63%
“…The deduction was further supported by the migration link from Europe to East China in the diffusion processes of VI.2.1.1.2.2 PPMV-1. Previous studies demonstrated that the European continent was the epicenter of global dissemination of PPMV-1 due to the movement of pigeons [39,40]. Cai et al [16] also proved that the VI viruses (P4 and W4) of China originated in Europe.…”
Section: Discussionmentioning
confidence: 99%